2009
DOI: 10.1186/1472-6904-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factor management of patients treated on an internal nephrology ward: a pilot study

Abstract: Background: The objectives of this pilot study were to evaluate treatment quality for the risk factors of hypertension, diabetes and hyperlipidemia as well as the overall treatment quality for patients on an internal nephrology ward. This evaluation included the collection of data concerning the quality of therapeutic drug monitoring, drug use and potential drug-drug interactions. Establishing such baseline information highlights areas that have a need for further therapeutic intervention and creates a foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In our study, we showed that multiple drug regimens were needed more with advanced CKD stages, as already demonstrated in a cross-sectional observational Swiss survey including diabetic and CKD patients visiting PCPs [45]. Multimedication and comorbidities are a cause of nonadherence to treatment [46], which could be improved by single pill combination therapy and clinical pharmacist evaluation of adverse effects and drug interactions [45].…”
Section: Blood Pressuresupporting
confidence: 69%
“…In our study, we showed that multiple drug regimens were needed more with advanced CKD stages, as already demonstrated in a cross-sectional observational Swiss survey including diabetic and CKD patients visiting PCPs [45]. Multimedication and comorbidities are a cause of nonadherence to treatment [46], which could be improved by single pill combination therapy and clinical pharmacist evaluation of adverse effects and drug interactions [45].…”
Section: Blood Pressuresupporting
confidence: 69%